(untitled) (Zaporizhzhia Historical Review, 2021)
The foundation of the legal, democratic, social state in Ukraine demands modern methods of political advertising in the management of the society. The political aspects of modern advertising in the world and in Ukraine, the establishment of global and domestic political advertising are examined in the article. The question of modern innovative technologies in the field of political advertising ar relevant and is the evidence of politics and management connection. The process of global political advertising establishment is analyzed. An opportunity to carry the political management out testifies that the level of personnel at the present stage changes, responsibility and communication connection between politics and state management achieves a good pace.